Rancang Bangun dan Analisis Kinerja Turbin Angin Sumbu Vertikal Modifikasi Menggunakan Empat Buah Blade - Habibie, Habibie; Lapisa, Remon; Irzal, Irzal; Abadi, Zainal (MASALIQ, 2024)
The island country is a characteristic of Indonesia, and is located right on the equator stretching from the island of Sumatra to the island of West Papua. The need for electrical energy is increasing, but the energy generally used to produce electrical energy is fossil energy, and the problem faced by most countries, including Indonesia, is the problem of energy reduction. According to the International Energy Agency (IEA), the electricity needed is 14 terawatts per day, arguably the equivalent of 210 million barrels of oil. The objectives of this research are (1) to design a wind turbine using fiberglass as the basic material, (2) to make a turbine that can utilize wind energy for electricity generation purposes, and (3) to determine the performance of a modified 4-blade vertical wind turbine on the power it produces. can be generated. The type of research carried out uses experimental methods. The test results show that wind turbines made from fiberglass are able to achieve wind turbine efficiency of 50.7%. The conclusion drawn is that the researchers succeeded in designing a wind turbine from fiberglass as the basic material, the wind turbine can rotate properly and can produce electricity. The generator power produced increases as the wind speed increases. A wind turbine using 4 blades at a wind speed of 21.6 m/s, produces a rotation per minute of 250.6 rpm, produces 108.20 watts and a torque of 107.14 Nm.